2009
DOI: 10.1088/0031-9155/54/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations to assess the effects of tube current modulation on breast dose for multidetector CT

Abstract: Tube current modulation was designed to reduce radiation dose in CT imaging while maintaining overall image quality. This study aims to develop a method for evaluating the effects of tube current modulation (TCM) on organ dose in CT exams of actual patient anatomy. This method was validated by simulating a TCM and a fixed tube current chest CT exam on 30 voxelized patient models and estimating the radiation dose to each patient’s glandular breast tissue. This new method for estimating organ dose was compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 29 publications
3
101
1
Order By: Relevance
“…Facilities that adjust their CT technique appropriately for patient size, whether with use of manual technique charts or automatic exposure control ( 35,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), will prescribe a wide range of scanner output (CTDI) values. This is a good outcome, refl ecting the facility's conscientiousness in "right-sizing" the dose settings on the basis of specifi c patient body habitus.…”
Section: Editorial: Ct Dose Index and Patient Dosementioning
confidence: 99%
“…Facilities that adjust their CT technique appropriately for patient size, whether with use of manual technique charts or automatic exposure control ( 35,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), will prescribe a wide range of scanner output (CTDI) values. This is a good outcome, refl ecting the facility's conscientiousness in "right-sizing" the dose settings on the basis of specifi c patient body habitus.…”
Section: Editorial: Ct Dose Index and Patient Dosementioning
confidence: 99%
“…11,12 As a result, the reported CTDI vol -to-organ-dose conversion coefficients were valid only for that specific scan protocol and patient model. Several investigators [13][14][15][16] have demonstrated that patient size has a significant effect on the absorbed dose and, even more specifically, on organ dose for a specific scanner output ͑e.g., CTDI vol ͒. These reports have all shown that for the same exposure conditions ͑i.e., same technical parameter settings͒, organs in smaller patients ͑including pediatric patients͒ receive higher radiation doses than those in larger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus to limit the radiation dose, low-dose computed tomography (LDCT) could be applied for screening in patients at high risk for developing lung cancer [4]. Low dose CT can be achieved by decreasing the milliamperage and the voltage [5][6], which, however, leads to a degraded signal to noise ratio [7][8][9][10][11]. This is due to a severe increase of the quantum and electronic noise.…”
Section: Introductionmentioning
confidence: 99%